Some Difficulties to Protect Agricultural Land from Conversion - Laksana, Satya (Bappenas Working Papers, 2020)
One of the most worrying global issues facing agricultural interests today is the rapid conversion of productive agricultural land to non-agricultural uses. Indonesia has enacted the Sustainable Agriculture Land Protection Law (Lahan Pertanian Pangan Berkelanjutan / LP2B) as a crucial section of the Spatial Planning Regulations. Furthermore, the law has been ratified by a number of regional regulations. However, there are still misconceptions about LP2B among stakeholders which can magnify the difficulty of implementing the regulation. Using the historical method, this descriptive paper elaborates difficulties in protecting agricultural land due to misconceptions of stakeholders within the case study in Tasikmalaya Regency, West Java Province, Indonesia. Misconceptions of stakeholders encompass three aspects: (1) land ownership (2) determination process and (3) implementation of LP2B protection. Difficulties did not automatically cease when the regulations had just enacted, instead, they continue into the application stage and become discourses in various cross-institutional forums. Furthermore, this paper synthesizes the author's own conceptions to rectify the misconceptions based on academic references and relevant statutory arguments. Stakeholders referred to in this paper were bureaucrats in agricultural and other institutions related to LP2B including the Regional Development Planning Agency, and the Ministry of Spatial Planning / National Land Agency. They were represented by officials, bureaucrats, or personnel who together with the author attended various coordination meetings, dissemination, workshops, focus group discussions, and similar forums that discussing LP2B and or other related topics in the period of 2014-2019. Policy implications are discussed